2017
DOI: 10.1128/aem.02786-16
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the Genome of Brochothrix thermosphacta, a Problematic Meat Spoilage Bacterium

Abstract: Brochothrix thermosphacta is a dominant but poorly studied meat spoilage organism. It is a close relative of the foodborne pathogen Listeria monocytogenes, and Brochothrix constitutes the second genus in the Listeriaceae family. Here, the genomes of 12 B. thermosphacta strains were sequenced, assembled into draft genomes, characterized, and compared with the genomes of Brochothrix campestris and L. monocytogenes. Phenotypic properties including biogenic amine production and antibiotic and heavy metal susceptib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(50 citation statements)
references
References 88 publications
3
44
0
Order By: Relevance
“…Therefore, the presence in the LM of WHWTs of these 2 genera could activate the immune system, alter the airway epithelium and induce or perpetuate the airway inflammation in CIPF. Little is known about the metabolism and the potential pathogenic role of bacteria of the Brochothrix, Pseudarcicella, Rhodoluna and Limnohabitans genera [28,30,31,[36][37][38]. Data of the present study showed that both healthy and CIPF WHWTs had a distinct microbiota compared with other healthy domestic dogs.…”
Section: The Lm In Cipf Whwtsmentioning
confidence: 51%
See 1 more Smart Citation
“…Therefore, the presence in the LM of WHWTs of these 2 genera could activate the immune system, alter the airway epithelium and induce or perpetuate the airway inflammation in CIPF. Little is known about the metabolism and the potential pathogenic role of bacteria of the Brochothrix, Pseudarcicella, Rhodoluna and Limnohabitans genera [28,30,31,[36][37][38]. Data of the present study showed that both healthy and CIPF WHWTs had a distinct microbiota compared with other healthy domestic dogs.…”
Section: The Lm In Cipf Whwtsmentioning
confidence: 51%
“…Rhodoluna and Limnohabitans genera were also found in higher relative abundance in WHWTs compared with domestic dogs from other breeds, but were higher in H-WHWTs than in D-WHWTs. These bacteria preferentially contaminate food (Brochothrix [28]) and water (Curvibacter [29], Rhodoluna [30], Limnohabitans [31], and Flavobacteriaceae_genus [32]), and can be ingested by dogs. Their presence in the LM of WHWTs could be associated with the higher abundance of gastroesophageal reflux reported in that breed compared with other breeds [33].…”
Section: The Lm In Cipf Whwtsmentioning
confidence: 99%
“…Other studies also described how B. thermosphacta steadily increases its levels in fresh meats during refrigerated storage under vacuum and anaerobic MAP, becoming one of the dominant spoilage species and originating cheesy, buttery, or sour odors [34]. According to Samelis [35], the levels of B. thermosphacta associated to fresh meat spoilage are around 7 Log CFU/g.…”
Section: Water Activity Ph Microbial Contents and Biogenic Amine Pmentioning
confidence: 99%
“…The most represented was Brochotrix thermosphacta, that accounted for 42% of the colonies. This dominant spoilage organism is responsible for deterioration of refrigerated meat products, harboring the genes involved in the production of malodorous compounds such as acetate, acetoin, butanediol, and fatty acids (Stanborough et al, 2017). Other major PCA isolates were LAB belonging to the species L. mesenteroides (15%), L. carnosum (13%), and Carnobacterium divergens (7%).…”
Section: Identification Of the Isolates At The End Of The Shelf Lifementioning
confidence: 99%